Pengaruh Citra Merek dan Kualitas Produk terhadap Keputusan Pembelian Skincare Scarlett pada Mahasiswa Kota Medan - Anjelina Padang; Vivianti Novita; Martolop Sinambela; Safaruddin Safaruddin; Nursiah Fitri (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
Brand image has an important role in purchasing decisions. It is related, when the product image has a strong value in the market, it can attract purchasing decisions. Product quality indirectly provides good product quality to customers so that if product consumers have good quality, this will enable consumers to make purchase decisions. This study aims to obtain empirical evidence on how the influence of brand image and product quality on purchasing decisions for scarlett skincare on students in Medan City. The research method used is a quantitative research method. Sampling was carried out using the incidental sampling technique with a total of 96 respondents and data collection was carried out by distributing questionnaires. The data analysis technique used is multiple linear regression with the help of SPSS version 26 statistical tools. Where the results of the study show: (1) brand image has a positive and significant effect on the decision to purchase Scarlet skincare (2) product quality has a positive and significant effect on the decision to purchase Scarlett skincare (3) simultaneously brand image and product quality have a positive and significant effect on the decision to purchase Scarlett skincare and (5) the results of the determination coefficient test (R Square) can be seen that Brand Image and Product Quality provide 63.3% in the decision to purchase Scarlet skincare for Medan City students while the remaining 33.7% is influenced by other factors from outside the study.